Analysis of the current status and associated risk factors of cognitive function in Tibetan hypertensive patients at various altitudes - Long Yin; Xiaoming Zhang; Huijuan Zhang; Ruizhen Li; Jing Zeng; Kaixuan Dong; Yi Wang; Xinghui Li (Clinical and Experimental Hypertension)
Objective This study aims to explore the current cognitive status and identify risk factors associated with cognitive function in Tibetan hypertensive patients living at various altitudes.Methods The Simple Mental Status Scale (MMSE) was used to evaluate the cognitive function of 611 Tibetan hypertensive patients at various altitudes in Gannan Tibetan Autonomous Prefecture. Afterward, we conducted an analysis to identify the factors influencing their cognitive function.Results The study found that the prevalence of cognitive dysfunction was 22.3%, with a higher incidence at high altitude (group D 29.0%) compared to low altitude (group A 16.0%). The study conducted a binary logistic regression analysis to identify the risk factors for cognitive dysfunction. The analysis revealed that altitude, age, body mass index, marital status, education, income level, and blood pressure control level were all significant risk factors. After controlling for age, body mass index, marital status, educational level, income level, and blood pressure control level, the risk of developing cognitive dysfunction was 2.773 times higher (p < .05) for individuals in group C at high altitude and 2.381 times higher (p < .05) for individuals in group D at high altitude compared to those in group A at low altitude.Conclusions Altitude plays a role in the development of cognitive dysfunction in hypertensive patients. Tibetan hypertensive patients living at high altitudes may be at a higher risk of cognitive dysfunction compared to those living at lower altitudes. Therefore, interventions should be targeted to prevent or mitigate potential cognitive impairment.